Sugar-sweetened beverage intake and chronic low back pain - Wang, Yanting; Tang, Yuchen; Li, Zhichun; Jiang, Changhai; Jiang, Wei; Hu, Zhenming (Frontiers in Nutrition, 2024)
The consumption of sugar-sweetened beverages (SSBs) has become a major public health problem globally. However, no studies have specifically examined the relationship between SSB intake and chronic low back pain (CLBP). Therefore, the present study aimed to investigate the relationship between SSB intake and the risk of CLBP.This cross-sectional study enrolled participants aged 20 to 69 from the National Health and Nutrition Examination Survey. CLBP was defined as persistent LBP for a consecutive threemonth period. Furthermore, SSB intake was assessed and calculated based on dietary recall interviews. Moreover, survey-weighted logistic regression models were employed to evaluate the association between SSB intake and the risk of CLBP, while the restricted cubic spline (RCS) analysis was used to determine whether there were nonlinear associations between SSB intake and CLBP risk. In addition, subgroup analysis was performed using stratification and interaction analysis for all covariates.Results: A total of 4,146 participants (mean age: 43.405 years) were enrolled in the final analysis. The results of survey-weighted logistic regression models showed that SSB consumption was significantly associated with an increased risk of CLBP among individuals aged 20 to 69 years. Moreover, the results of subgroup analysis and interaction analysis demonstrated that the association between SSB intake and the risk of CLBP was modified by smoking status and hypertension. Specifically, the SSB intake-associated CLBP risk was more pronounced among current smokers or individuals with hypertension.Conclusions: Reduction of SSB consumption might contribute to the prevention of CLBP for individuals aged 20 to 69 years. Moreover, current smokers or individuals with hypertension should be more vigilant about the SSB intake-associated CLBP risk. Nevertheless, caution should be exercised when interpreting the results of this study, as further research is necessary to explore the association between SSB consumption and CLBP, given the limitations of the current study.